3D Macroporous Zinc Compound/Silicone Hybrid Foams for Amperometric Sensing of Glucose Oxidase. Issue 2 (25th November 2018) - Wu, Ye; Fu, Hao; Xie, Weiwei; Lin, Yingcheng; Kizilkaya, Orhan; Xu, Jian
Abstract: A 3D porous matrix makes an intriguing sensing platform, which can integrate functional guest molecules. Here, the first demonstration of a zinc compound/silicone hybrid foam is reported for amperometric sensing of glucose oxidase. The silicone foam is fabricated by a self‐developed solid‐filling‐melting method. Two zinc‐based polymers, Zn‐Compound‐1 and Zn‐Compound‐2, are synthesized. Zn‐Compound‐1 and Zn‐Compound‐2 are characterized by X‐ray diffraction, X‐ray photoelectron spectroscopy, Fourier‐transform infrared spectroscopy, Raman spectroscopy, and X‐ray absorption nearedge structure spectroscopy of carbon K‐edge, oxygen K‐edge, and zinc L‐edge. Effective amperometric sensing of glucose oxidase is achieved by introducing Zn‐Compound‐1 or Zn‐Compound‐2 into the silicone foam, i.e., an increase of the concentration of the glucose oxidase led to an increase of detected current. This phenomenon can be explained by a possible mechanism of the formation of electron extra bands. Abstract : The Zn‐compound/silicone hybrid foam can be used for amperometric glucose oxidase sensing. This effect is possibly due to the formation of extra bands. In terms of the use of simple chemistry and facile fabrication, the technique may provide a rapid method to fabricate field detection devices for a variety of biochemical sensing/analysis applications.